2013
DOI: 10.4269/ajtmh.12-0691
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing Fever Borreliae in Africa

Abstract: Abstract. The study of relapsing fever borreliae in Africa has long suffered from the use of non-specific laboratory tools for the direct detection of these spirochetes in clinical and vector specimens. Accordingly, Borrelia hispanica, Borrelia crocidurae, Borrelia duttonii, and Borrelia recurrentis have traditionally been distinguished on the basis of geography and vector and the unproven hypothesis that each species was exclusive to one vector. The recent sequencing of three relapsing fever Borrelia genomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 48 publications
0
50
0
Order By: Relevance
“…38 To the best of our knowledge, Borrelia spp., a fastidious bacterium, has for the first time been detected in Gabon, in afebrile children, while the spread of some species such as Borrelia duttonii, Borrelia recurrentis, and Borrelia crocidurae have recently been limited in other sub-Saharan African countries. 15 The biggest problem with the studies previously reported is that they did not use control groups to conclude the fever etiology related to a microorganism. Asymptomatic carriage of some bacteria such as Staphylococcus aureus, R. felis, and P. falciparum in afebrile people was reported in sub-Saharan Africa countries.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…38 To the best of our knowledge, Borrelia spp., a fastidious bacterium, has for the first time been detected in Gabon, in afebrile children, while the spread of some species such as Borrelia duttonii, Borrelia recurrentis, and Borrelia crocidurae have recently been limited in other sub-Saharan African countries. 15 The biggest problem with the studies previously reported is that they did not use control groups to conclude the fever etiology related to a microorganism. Asymptomatic carriage of some bacteria such as Staphylococcus aureus, R. felis, and P. falciparum in afebrile people was reported in sub-Saharan Africa countries.…”
Section: Resultsmentioning
confidence: 77%
“…8 Recent studies performed in western sub-Saharan Africa have shown the role of emergent and fastidious bacteria, such as Rickettsia felis, Coxiella burnetii, Tropheryma whipplei, Borrelia crocidurae, and Bartonella spp., as the cause of fever. [9][10][11][12][13][14][15] Rickettsia felis and Borrelia duttonii were also found in eastern Africa. [16][17][18] Some of them had already been described in Gabon.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Borrelia is essentially composed of the Lyme disease group and the relapsing fever group (123)(124)(125). Many Borrelia species, particularly those species of the Lyme disease group, are routinely cultured in liquid Barbour-Stoenner-Kelly II (BSK-II) medium under microaerophilic conditions (126,127) or its variations, such as BSK-H (128), at 30°C to 34°C.…”
Section: Spirochetesmentioning
confidence: 99%
“…2 Borrelia crocidurae has been detected with a 2.5% prevalence in Ornithodoros sonrai ticks, 3 while Lyme group Borrelia garinii was recently detected in Ixodes ricinus ticks, collected from El Ghora, Algeria. 4 In addition, at least 10 different relapsing fever-causing borreliae have been documented in Africa, including five different borreliae in humans and five different borreliae in nonhuman hosts.…”
mentioning
confidence: 99%
“…4 In addition, at least 10 different relapsing fever-causing borreliae have been documented in Africa, including five different borreliae in humans and five different borreliae in nonhuman hosts. 2 The former includes pathogens classified as B. hispanica, B. crocidurae, B. duttonii, and B. recurrentis.…”
mentioning
confidence: 99%